Pengaruh Mutasi dan Remunerasi terhadap Loyalitas Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi pada Lingkungan KPP Pratama Jember - Setyawan, Ari; Susbiyani, Arik; Satoto, Eko Budi (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to analyze the influence of mutation and remuneration on job satisfaction and employee loyalty at the Tax Office (KPP) Pratama Jember. The research method used is quantitative descriptive with data collection using a sample of all employees of KPP Pratama Jember totaling 93 samples. Data analysis is carried out using Variance-based Structural Equation Modeling (SEM-PLS) with the assistance of Warp PLS V.8.0. The results of the study show that mutation has a significant positive effect on job satisfaction, as well as remuneration. Job satisfaction also has a strong positive impact on employee loyalty. This finding emphasizes that good management of mutation and remuneration can increase employee satisfaction and loyalty in the tax institution. Path analysis results show significant direct and indirect influences among variables. Mutation and remuneration affect job satisfaction, while job satisfaction becomes a significant mediator in the relationship between mutation, remuneration, and employee loyalty. This research contributes to understanding the factors that influence job satisfaction and employee loyalty in the tax institution environment. Managerial implications include the expa This study aims to analyze the influence of mutation and remuneration on job satisfaction and employee loyalty at the Tax Office (KPP) Pratama Jember. The research method used is quantitative descriptive with data collection using a sample of all employees of KPP Pratama Jember totaling 93 samples. Data analysis is carried out using Variance-based Structural Equation Modeling (SEM-PLS) with the assistance of Warp PLS V.8.0. The results of the study show that mutation has a significant positive effect on job satisfaction, as well as remuneration. Job satisfaction also has a strong positive impact on employee loyalty. This finding emphasizes that good management of mutation and remuneration can increase employee satisfaction and loyalty in the tax institution. Path analysis results show significant direct and indirect influences among variables. Mutation and remuneration affect job satisfaction, while job satisfaction becomes a significant mediator in the relationship between mutation, remuneration, and employee loyalty. This research contributes to understanding the factors that influence job satisfaction and employee loyalty in the tax institution environment. Managerial implications include the expansion of transparent mutation policies and a fair remuneration system to support career development and employee satisfaction. Thus, the results of this study can serve as a basis for strategic and managerial improvements in efforts to maintain and enhance employee performance at KPP Pratama Jember. Keywords: Employee Loyalty, Job Satisfaction, Mutation, Remuneration, Tax Office (KPP) Pratama Jember. nsion of transparent mutation policies and a fair remuneration system to support career development and employee satisfaction. Thus, the results of this study can serve as a basis for strategic and managerial improvements in efforts to maintain and enhance employee performance at KPP Pratama Jember. Keywords: Employee Loyalty, Job Satisfaction, Mutation, Remuneration, Tax Office (KPP) Pratama Jember.